1984
DOI: 10.1136/gut.25.10.1103
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic measurement of oesophageal transmucosal potential difference in reflux oesophagitis.

Abstract: SUMMARY Oesophageal transmucosal potential difference (PD) was measured in 76 patients during endoscopy. Twelve patients with no symptoms of gastro-oesophageal reflux, and normal oesophageal appearance on endoscopy and mucosal biopsy had a PD of -18.3±3 8 mV (mean + SD). Thirty three patients had reflux symptoms but the oesophagus appeared normal at endoscopy. Eighteen of these patients had reflux change on oesophageal suction biopsies and the PD in the same region of the oesophagus in this group was -18.1±7*5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In the columnar epithelium of Barrett's esophagus the transmucosal potential difference is more negative than that in normal squamous epithelium . Although in patients with erosive reflux disease PD was less negative than that in healthy controls, in patients with mild or absent erosions the esophageal transmucosal potential difference was not significantly different from that in healthy controls, which made this technique not suitable for further development as an investigational tool for GERD …”
Section: Discussionmentioning
confidence: 94%
“…In the columnar epithelium of Barrett's esophagus the transmucosal potential difference is more negative than that in normal squamous epithelium . Although in patients with erosive reflux disease PD was less negative than that in healthy controls, in patients with mild or absent erosions the esophageal transmucosal potential difference was not significantly different from that in healthy controls, which made this technique not suitable for further development as an investigational tool for GERD …”
Section: Discussionmentioning
confidence: 94%
“…This technique is useful to detect changes in the integrity of the mucosa of GERD patients with severe esophagitis but it fails in patients with mild esophagitis and NERD. [75][76][77][78] Moreover, according to Ohm's law (PD = I/R), the PD does not only reflect the integrity of the tissue, as changes in PD may also occur when changes in secretion arise. Then, TMPD is not a good tool for studying mucosal integrity in NERD patients or in refractory patients, in whom esophageal lesions are normally absent due to acid suppression therapy.…”
Section: Functional Evaluation Of Esophageal Mucosa Integritymentioning
confidence: 99%
“…Transmucosal electrical potential difference (TMPD) measurements have been used until end of the 1990's to evaluate the status of the mucosal integrity in vivo . This technique is useful to detect changes in the integrity of the mucosa of GERD patients with severe esophagitis but it fails in patients with mild esophagitis and NERD . Moreover, according to Ohm's law (PD = I/R), the PD does not only reflect the integrity of the tissue, as changes in PD may also occur when changes in secretion arise.…”
Section: Functional Evaluation Of Esophageal Mucosa Integritymentioning
confidence: 99%
“…Animal studies in rabbits show that luminal acid alters sodium transport, changing the PD . TMPD is abnormal in patients with EE, but this is not the case when endoscopic findings are normal . A recent study from Orlando's group using in vitro measurements indicated that impaired integrity is not only present in eroded areas of patients with EE, but also in areas without lesions as was indicated by a decreased transepithelial resistance (TEER) and an increased passage of fluorescein.…”
Section: Intraluminal Impedance In the Evaluation Of The Esophageal Mmentioning
confidence: 99%